Patient-Reported Outcomes in Robotic-Assisted vs Manual Cementless Total Knee Arthroplasty - Michael J. Stoltz, MD; Nolan S. Smith, MD; Sarag Abhari, MD; John Whitaker, MD; James F. Baker, MD; Langan S. Smith, BS; Rohat Bhimani, MD; Madhusudhan R. Yakkanti, MD; Arthur L. Malkani, MD (Arthroplasty Today)
Background: Robotic-assisted total knee arthroplasty (RA-TKA) was introduced to provide surgeons with virtual preoperative planning and intraoperative information to achieve the desired surgical goals in an effort to improve patient outcomes. The purpose of this study was to compare clinical outcomes and patient-reported outcome measures following primary TKA using RA-TKA vs manual instrumentation. Methods: This was a retrospective cohort review study comparing 393 primary RA-TKAs vs 312 manual TKAs at a minimum 2-year follow-up. The same cementless implant design was utilized in all cases at a single institution. There were no significant differences in age or gender between groups. Outcome measures included range-of-motion, Knee Society (KSS), Western Ontario and McMaster Universities Osteoarthritis Index, Forgotten Joint Score-12, Knee Injury and Osteoarthritis Outcome Score for Joint Replacement, and overall patient satisfaction scores along with complications and survivorship. Results: Compared to manual TKA, the RA-TKA group had significant higher postoperative KSS Function and Knee scores, Western Ontario and McMaster Universities Osteoarthritis Index, and Knee Injury and Osteoarthritis Outcome Score for Joint Replacement scores (P < .001). A total percentage of 95.0% of RA-TKA vs 87.4% of manual TKAs were very satisfied or satisfied (P = .001). Survivorship with all-cause failure as the endpoint at 3 years was 96.9% in the RA-TKA group compared to 95.8% in the manual group (P = .54). Conclusions: RA-TKA demonstrated significant improvement over manual jig-based instruments in KSS Function, KSS Knee, Western Ontario and McMaster Universities Osteoarthritis Index, Knee Injury and Osteoarthritis Outcome Score for Joint Replacement, and patient satisfaction scores following primary TKA with no differences in complications and revision incidence. RA-TKA provided a virtual 3-dimensional preoperative plan along with intraoperative information for adjustments to approximate the patients' native joint line and achieve a well-balanced soft-tissue sleeve about the knee for primary TKA.